Relation between population density and topology in potable water distribution networks (2017)
"One of cities basic needs is water supply, which is function of their inhabitant?s number and density. However, population varies with time, due to changes in building occupancy and those differences generate uncertainty about the hydraulic behavior of Water Distribution Systems (WDS). This study presents a correlation analysis between the population density and the topology of potable WDS by means of four real networks, chosen for their geometric shape, located in Colombia (in the regions of Valle del Cauca and Cundinamarca). The procedure can be summarized in three steps: i) Analysis of initial conditions: populations and initial supply flows were analyzed and the geometry of each WDS was evaluated; ii) Design of the WDS with different increases in population densities: were established five different designs which were executed using the Optimal Power Use of Surface (OPUS) methodology; iii) Analysis, location and verification of network rating indexes: The network hydraulics were verified by means of pressure surfaces and pipe diameters; besides, reliability and energy efficiency indexes were calculated; the created geometric centroids were calculated and located; a water quality study was made by verifying changes in water age and chlorine initial concentration in the tank; finally, the variation of cost per cubic meter of water transported and the fractality of the WDS was studied. The results showed that increases in population density did not necessarily lead to significant variations of the geometric parameters, that the reliability and energy efficiency indicators remained almost constant and that the variation of diameters was not uniform for all the pipe sections of the system. The chlorine initial concentration in the tank increased and the age of the water decreased, the costs per cubic meter transported also dropped and the fractality of the networks was not affected."--Tomado del Formato de Documento de Grado.